The changing face of meningococcal infection. (November 2021) - Knapper, Francesca
Highlights: Menigococcal infection is caused by Neisseria meningitidis. Invasive meningococcal disease (IMD) has a case fatality of between 4 and 20% Clonal expansion of hypervirulent strains has been seen in epidemics. Vaccination against Men ACWY and MenB has been part of the childhood schedule in the UK since 2015. Over the last 1o years rates of invasive meningococcal disease in the UK have fallen by over 50%. Abstract: Menigococcal infection is caused by Neisseria meningitidis, a Gram negative diplococci. Invasive meningococcal disease (IMD) is caused by 6 capsular groups. The spectrum of infection is broad, with meningitis and meningococcal sepsis associated with a case fatality of between 4 and 20%. The main burden of disease is felt in the under 1′s and this is where vaccination has been focused. Vaccination against MenC begun in 1999, with vaccines against Men ACWY and MenB added to the schedule in 2015. Over the last 1o years rates of IMD in the UK have fallen by over 50%. The impact of COVID-19 on cases has also been felt, with early data suggesting a significant drop in cases during the first wave in 2020. Despite the success of vaccination we need to remain vigilant. Clonal expansion of hypervirulent strains has been seen in epidemics and we have a significant proportion of the population who remain unvaccinated.